1995
DOI: 10.1002/jsfa.2740680408
|View full text |Cite
|
Sign up to set email alerts
|

Effect of condensed tannin in cottonseed hulls on endogenous ileal amino acid loss in the growing rat

Abstract: The effect of condensed tannin (CT) in cottonseed hulls (CSH) on endogenous ileal amino acid flow in the growing rat was evaluated. CSH contain around 900g kg-' fibre and 52 g kg-' total CT. Twenty-four rats were allocated to four semi-synthetic diets, which contained enzymically hydrolysed casein (EHC) as the sole source of dietary nitrogen and chromic oxide as an indigestible marker. Two of the diets contained no CSH while the remaining two contained 50gkg-' CSH. At each level of hull inclusion (0 and 50gkg-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1996
1996
1998
1998

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Thus, PEG can be used to displace protein from the CT-protein complexes without affecting the nutritional composition of the diet (Jones & Mangan, 1977). Previous studies with PEG have shown that PEG addition per se had no intrinsic effect on protein digestibility in the absence of CT (Yu et al 1995b(Yu et al , 1996b. In the present study it was assumed that PEG completely bound with the CT released during digestion of the diets containing cottonseed hulls and CSM, and comparison between diets including or not including PEG allowed the effect of cottonseed CT to be defined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, PEG can be used to displace protein from the CT-protein complexes without affecting the nutritional composition of the diet (Jones & Mangan, 1977). Previous studies with PEG have shown that PEG addition per se had no intrinsic effect on protein digestibility in the absence of CT (Yu et al 1995b(Yu et al , 1996b. In the present study it was assumed that PEG completely bound with the CT released during digestion of the diets containing cottonseed hulls and CSM, and comparison between diets including or not including PEG allowed the effect of cottonseed CT to be defined.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary CT have been shown to reduce bodyweight gain, impair feed conversion efficiency and reduce the apparent digestibility of protein and amino acids in single-stomached species (Longstaff & McNab, 1991 ;Jansman, 1993;Yu et al 199621). Our previous work with the growing rat has shown that the addition of cottonseed hulls to a semi-purified diet significantly increased endogenous ileal amino acid loss (Yu et al 1995b), whilst hulls, partly due to their CT content, decreased the apparent and true ileal digestibility of amino acids in cottonseed kernel (Yu et al 1996b).…”
mentioning
confidence: 97%